Profitability Moderates the Effects of Institutional Ownership, Dividend Policy and Free Cash Flow on Debt Policy - Fitriyani, Ulfi Nihayah; Khafid, Muhammad (Accounting Analysis Journal, 2019)
This study analyzes the influence of institutional ownership, dividend policy, and free cash flow on debt policy with profitability as moderating. The study population was 148 manufacturing sector companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The samples obtained were 41 companies with 123 units of analysis with purposive sampling method on predetermined criteria. Data were analyzed with SPSS 21 application with moderation regression analysis method. Institutional ownership and dividend policy have no significant effect on debt policy. Meanwhile, free cash flow has a significant positive effect on debt policy. In addition, profitability cannot moderate the significant influence of institutional ownership, dividend policy and free cash flow on debt policy is the result of research. The conclusion of this study is that companies need to improve the optimal debt policy to avoid financial difficulties in the future and the profitability ratio needs to be increased because increased debt use is determined by looking at the potential profitability of the company.